Preparation and Optical Property of Hierarchical Structured Porous ZnO Microplates - Shao, Guoquan; Fang, Xiumin; Xu, Chang; Wei, Liangqin (Asian Journal of Chemistry, 2014)
Hierarchical structured porous ZnO microplates have been prepared by thermal decomposition of Zn5(CO3)2(OH)6 precursor. The products are characterized by X-ray diffraction, field-emission scanning electron microscopy, high resolution transmission electron microscopy, transmission electron microscopy, UV-visible absorption spectrum and photoluminescence spectra. Each ZnO microplate is made up of nanoparticle-based nanowires with diameters of 40-80 nm and lengths of 2-3 μm and the diameter of constituent nanoparticles ranges from 10 to 20 nm. Due to their porous hierarchical microstructures, the prepared ZnO products exhibit excellent optical properties.